The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1477-5956-10-60
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Coded Protein Labeling analysis of plasma specimens from acute severe dengue fever patients

Abstract: BackgroundDengue fever is the most important arthropod born viral disease of public health significance. Although most patients suffer only from flu-like symptoms, a small group of patient experiences more severe forms of the disease. To contribute to a better understanding of its pathogenesis this study aims to identify proteins differentially expressed in a pool of five viremic plasma from severe dengue patients relative to a pool of five non-severe dengue patients.ResultsThe use of Isotope Coded Protein Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Consistent with this possibility, in our study DHF/DSS cases had lower VDBP than controls, even though this difference was not statistically significant. Circulating VDBP might decrease in patients with severe dengue through reduced protein expression but this was not the case in one study of 10 patients [31]. An anecdotal report of five cases with DF suggested that the administration of vitamin D and calcium during the acute episode shortened the duration of disease [32]; thus, the potential therapeutic value of enhancing vitamin D bioavailability during acute dengue infection requires careful consideration in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, in our study DHF/DSS cases had lower VDBP than controls, even though this difference was not statistically significant. Circulating VDBP might decrease in patients with severe dengue through reduced protein expression but this was not the case in one study of 10 patients [31]. An anecdotal report of five cases with DF suggested that the administration of vitamin D and calcium during the acute episode shortened the duration of disease [32]; thus, the potential therapeutic value of enhancing vitamin D bioavailability during acute dengue infection requires careful consideration in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , regulation windows varied between +1.39 to +2.29, depending on the combination of ICPL tags used for comparison. This determination of exclusion criteria is similar to other studies that have adopted a normalized expression differences of one or two SD, used arbitrary assigned transformed intensity ratios, or experimentally determined ICPL Heavy/Light ratio values. , …”
Section: Resultsmentioning
confidence: 81%
“…This determination of exclusion criteria is similar to other studies that have adopted a normalized expression differences of one or 44 two SD, 45 used arbitrary assigned transformed intensity ratios, 46 or experimentally determined ICPL Heavy/Light ratio values. 34,47 Partial characterization of the urine proteome by in-solution fractionation and LC-MS/MS Reaction with ICPL reagents (containing a nicotinoyloxysuccinimide group with deuterium and/or 13C substitutions) and εamino groups results in the loss of a basic side chain and a shift in the isoelectric point of basic peptides toward a more acidic pI. 36 We therefore applied isoelectric focusing on a pH 3−10 gradient, followed by refocusing of the most acidic fractions on a pH 3−6 gradient to evaluate the labeled urine proteins present.…”
Section: Determination Of a Control Regulation Window For Icpl Labeli...mentioning
confidence: 99%
“…The peptides of bacteria may be directly detectable in human serum using mass spectrometry (Cheung et al, 2015). It may be possible to detect the presence of infectious agents either via the host response or from the presence of the pathogen's own proteins (Fragnoud, Yugueros-Marcos, Pachot, & Bedin, 2012;Haverland, Villeneuve, Ciborowski, & Fox, 2016;Kruh-Garcia et al, 2014). Blood-based protein biomarkers for diagnosis of Alzheimer disease including VCAM1, ILGFBP2, Carcinoembryonic antigen, CD40, and macrophage inflammatory protein alpha 1 and SOD were discovered by screening with a panel of immunoassays (Doecke et al, 2012).…”
Section: Discovery Of Biomarkers By Mass Spectrometrymentioning
confidence: 99%